Effects of Qi-Fu-Yin on aging of APP/PS1 transgenic mice by regulating the intestinal microbiome - Xiao, Qiu-yue; Ye, Tian-yuan; Wang, Xiao-long; Qi, Dong-mei; Cheng, Xiao-rui (Frontiers in Cellular and Infection Microbiology, 2023)
Alzheimer's disease is the most common form of dementia and closely related to aging, but there is no cure for this serious neurodegenerative disease. Qi-Fu-Yin is widely used to treat dementia, but its anti-aging effects is unknown. Here we founded that Qi-Fu-Yin improved the ability of motor coordination, raised survival rate and prolonged the survival days under cold stress stimulation in aged APP/PS1 transgenic mice. Our data from 16sRNA and metagenomic sequencing showed that at the Family level, the intestinal microbiota was significantly different among wild-type mice, APP/PS1 transgenic mice and the Qi-Fu-Yin group by PCA analysis. Importantly, Qi-Fu-Yin improved the functional diversity of the major KEGG pathways, carbohydrate-active enzymes, and major virulence factors in the intestinal flora of APP/PS1 transgenic mice. Among them, the functions of eight carbohydrate-active enzymes (GT2_Glycos_transf_2, GT4, GT41, GH2, CE1, CE10, CE3, and GH24) and the functions of top three virulence factors (defensive virulence factors, offensive virulence factors and nonspecific virulence factors) were significantly and positively correlated with the level of grasping ability. We further indicated that the Qi-Fu-Yin significantly reduced the plasma levels of IL-6. Our results indicated that the effects of Qi-Fu-Yin anti-aging of APP/PS1 transgenic mice might be via modulating intestinal microbiome